NÃO-PREFERÊNCIA PARA OVIPOSIÇÃO E ALIMENTAÇÃO DE SPODOPTERA FRUGIPERDA (J. E. SMITH, 1797) (LEPIDOPTERA: NOCTUIDAE) POR CULTIVARES DE AMENDOIM - Campos, A.p. [UNESP]; Boiça, A.l. [UNESP]; Ribeiro, Z.a. [UNESP] (Instituto Biológico, 2020)
This study aimed to select peanut cultivars resistant to Spodoptera frugiperda, selecting non-oviposition and non-feeding preference in choice and no-choice tests. Peanut cultivars with upright growth habit (IAC 5, IAC 8112, IAC 22 and IAC Tatu ST) and runner growth habit (IAC 503, IAC 505, IAC 147, IAC 125, IAC Caiapó and IAC Runner 886) were evaluated. Tests of non-oviposition preference were conducted with newly emerged adults. Adults were fed a 10% honey solution, remaining in cages for 4 days until the start of the evaluations. The evaluations consisted of quantifying the number of eggs and egg masses, followed by calculating the number of eggs per egg mass. To perform non-feeding preference tests, leaf discs from different peanut cultivars were placed in disposable Petri dishes followed by releasing of a third-instar caterpillar for each cultivar. The attractiveness at 1, 5; 10, 15, 30, 60, 120, 360, 720 and 1,440 minutes was evaluated by counting the caterpillars that were feeding on cultivars. The leaf area consumed was evaluated at the end of the experiment for each cultivar. In the tests of non-oviposition and non-feeding preference, with choice or no-choice, none of the cultivars of the upright growth and runner growth habit influenced the oviposition or food of S. frugiperda. Thus, the peanut cultivars showed no resistance of the non-feeding and non-oviposition types.

Este trabalho buscou selecionar cultivares de amendoim resistentes a Spodoptera frugiperda, dos tipos não-preferência para oviposição e alimentação, em testes com e sem chance de escolha. Utilizaram-se cultivares de amendoim de hábitos de crescimento ereto (IAC 5, IAC 8112, IAC 22 e IAC Tatu ST) e rasteiro (IAC 503, IAC 505, IAC 147, IAC 125, IAC Caiapó e IAC Runner 886). Os testes de não-preferência para oviposição foram realizados com adultos recém-emergidos, os quais foram alimentados com solução de mel a 10%, permanecendo nas gaiolas por quatro dias até o início das avaliações. Estas consistiram na quantificação do número de ovos e posturas, com posterior cálculo do número de ovos por postura. Para os testes de não-preferência para alimentação foram colocados discos foliares das cultivares em placas de Petri, liberando uma lagarta de terceiro ínstar por cultivar. Avaliou-se a atratividade a 1, 5, 10, 15, 30, 60, 120, 360, 720; 1.440 minutos, contando-se o número de lagartas que se alimentavam nas cultivares e, ao término do experimento, quantificou-se a área foliar consumida por cultivar. Nos testes de não-preferência para oviposição ou alimentação, com ou sem chance, nenhuma cultivar de hábitos de crescimento ereto ou rasteiro influenciou a oviposição ou alimentação de S. frugiperda. Dessa maneira, as cultivares de amendoim não apresentaram resistência dos tipos não-preferência para oviposição e alimentação.
NON-OVIPOSITION AND NON-FEEDING PREFERENCE OFSPODOPTERA FRUGIPERDA(J. E. SMITH, 1797) (LEPIDOPTERA: NOCTUIDAE) FOR PEANUT CULTIVARS
Keywords: Fall armyworm; Arachis hypogaea; host plant resistance; types of resistance; Lagarta-do-cartucho; Arachis hypogaea; resistência de plantas; tipos de resistência